Effect of hydrothermal pre-treatment on ferulic acid content and antioxidant activities of corn hydrolysate - Sunisa Boonma (2018)
© 2018 Japan Society for Food Engineering. This study investigated the ef fect of hydrothermal pre-treatment on ferulic acid content and antioxidant activities of corn hydrolysate. The low-grade corn was treated by hot water and autoclaving process at different temperatures and times. The highest phenolic content (471.7±7.4 μg FA.mL-1, p＜0.05) was obtained by autoclaving at 121℃for 90 min. High performance liquid chromatography (HPLC) revealed 277.3±3.2 μg.mL-1of FA, which was 2.05 times higher than that of the control (unheated sample). The high yield of FA obtained here may be due to high-temperature autoclaving eliminating the FA-lignin and FA-polysaccharide bonds. Furthermore, the optimal hydrothermal pre-treatment at 121℃for 90 min improved the DPPH and ABTS radical scavenging activities by 1.3 and 1.5 fold, respectively, compared to the control. On the other hand, the dextrose equivalent (DE) values obtained from corn hydrolysate at the different heat treatments in this study were in the range of 23.2±0.7 to 28.7±0.9. These results illustrated that autoclaving method showed a promising pre-treatment process to add value of corn hydrolysate product.